Mantrālayam Carkuru Śrī Rākavēntira Svāmikaḷ : vāḻkkaīyum upatēcaṅkaḷum - Veṅkatrāv, K. (Kiṭaikkumiṭam Śrī Kurukirupā Patippakam, 1981)
On the life and teachings of Swami Rāghavēndra, 1601-1661, Madhava philosopher.